2021
DOI: 10.48550/arxiv.2105.14026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Energetic Explosions from Collisions of Stars at Relativistic Speeds in Galactic Nuclei

Abstract: We consider collisions between stars moving near the speed of light around supermassive black holes (SMBHs), with mass M • 10 8 M , without being tidally disrupted. The overall rate for collisions taking place in the inner ∼ 1 pc of galaxies with M • = 10 8 , 10 9 , 10 10 M are Γ ∼ 5, 0.07, 0.02 yr −1 , respectively. We further calculate the differential collision rate as a function of total energy released, energy released per unit mass lost, and galactocentric radius. The most common collisions will release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Several theoretical and computational studies have shown that destructive collisions can deplete the supply of stars near the SMBH (e.g., Duncan & Shapiro 1983;David et al 1987aDavid et al , 1987bMurphy et al 1991;Rauch 1999;Freitag & Benz 2002;Rose et al 2023). The frequency and outcomes of direct collisions depend on the distance from the SMBH (e.g., Lai et al 1993;Rauch 1999;Rubin & Loeb 2011;Hu & Loeb 2021;Rose et al 2023). This process may therefore have distinct effects on the stellar density profile (e.g., Rauch 1999;Freitag & Benz 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical and computational studies have shown that destructive collisions can deplete the supply of stars near the SMBH (e.g., Duncan & Shapiro 1983;David et al 1987aDavid et al , 1987bMurphy et al 1991;Rauch 1999;Freitag & Benz 2002;Rose et al 2023). The frequency and outcomes of direct collisions depend on the distance from the SMBH (e.g., Lai et al 1993;Rauch 1999;Rubin & Loeb 2011;Hu & Loeb 2021;Rose et al 2023). This process may therefore have distinct effects on the stellar density profile (e.g., Rauch 1999;Freitag & Benz 2002).…”
Section: Introductionmentioning
confidence: 99%